Action Research: Principles and practice, 3rd edition - McNiff, Jean (Routledge, 2020)
Since its first publication, Action Research: Principles and Practice has become a key text in its field. This new updated edition clearly describes and explains the practices of action research and its underlying values, and introduces important new ideas, including: